Influence Of Product Quality And Price Perception On Purchase Decision (Survey of Diva Furniture di Cibeureum, Tasikmalaya) - Selly Devi; Depy Muhamad Fauzy; Suci Putri Lestari (Journal of Indonesian Management, 2022)
This study aims to determine the effect of product quality and price perceptions on consumer purchasing decisions for Diva Furniture, Cibeureum, Tasikmalaya City. The method used is accidental sampling with a sample of 100 respondents. The analytical tool used in this research is path analysis. The results of this study indicate that product quality has a significant effect on consumer purchasing decisions for Diva Furniture, Cibeureum, Tasikmalaya City. Price perception has a significant effect on consumer decisions of Diva Furniture cibeureum tasikmalaya city. Product quality has a significant effect on purchasing decisions through consumer price perceptions of Diva Furniture, Cibeureum, Tasikmalaya.